2015
DOI: 10.1016/j.neurobiolaging.2014.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of β-amyloid and γ-secretase by calorie restriction in female Tg2576 mice

Abstract: Research indicates that female risk of developing Alzheimer’s disease (AD) is greater than that of males. Moderate reduction of calorie intake, known as calorie restriction (CR), reduces pathology in AD mouse models, and is a potentially translatable prevention measure for individuals at-risk for AD, as well as an important tool for understanding how the brain endogenously attenuates age-related pathology. Whether sex influences the response to CR remains unknown. In this study, we assessed the effect of CR on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 100 publications
(142 reference statements)
6
66
0
Order By: Relevance
“…Animal studies further demonstrated that Aβ plaque formation is an activity dependent process associated with AG [49, 51]. Therefore, increased oxidative metabolism in cognition-related regions may decrease AG and thus reduce the risk for AD, consistent with the findings in CR mice [23, 24]. …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Animal studies further demonstrated that Aβ plaque formation is an activity dependent process associated with AG [49, 51]. Therefore, increased oxidative metabolism in cognition-related regions may decrease AG and thus reduce the risk for AD, consistent with the findings in CR mice [23, 24]. …”
Section: Discussionsupporting
confidence: 63%
“…Enhanced memory in elderly humans and aging animals has also been reported with CR [1922]. In animal models of AD, CR reduces amyloid beta (Aβ) deposition and preserves memory [23, 24]. However, the impact of CR on CBF and BBB, and the interplay between in vivo neurovascular functions, cognitive aging, and mental health, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the different behavioral and cognitive demands, the series of attention tasks used in the present study required a more stringent and longer period of food restriction than the water maze procedure. A growing literature suggests that calorie restriction itself can be neuroprotective in mouse models of neurodegenerative disorders (Contestabile, 2009; Schafer et al, 2015a, 2015b), and thus may have interacted with the effects of MCS and/or the trisomy. BFCN morphometry may also have been influenced by social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, improvements in AD symptoms after caloric restriction, or a reduction in glucose dependent energy metabolism supports the hypothesis that a decrease in glucose metabolism is protective [31,32,605,606]. Overall, these observations identify glucose energy metabolism as an important target of study to improve our understanding of AD progression.…”
Section: Chapter # Viii: General Discussionsupporting
confidence: 56%